+0  
 
0
816
3
avatar+65 

(-6)^2/(-3)-8/(-1/2)-5  P.S Its very easy I know.

 Jun 3, 2015

Best Answer 

 #1
avatar+107456 
+10

$$\\\frac{(-6)^2}{(-3)}+\qquad\frac{-8}{(-1/2)}\qquad-5 \\\\
=\frac{36}{(-3)}+\qquad-8\div\frac{-1}{2}\qquad-5 \\\\
=\frac{36}{(-3)}+\qquad 8\div\frac{1}{2}\qquad-5 \qquad $A neg divided by a neg = a pos$\\\\
=-12+\qquad 8\times\frac{2}{1}\qquad-5 \\\\
=-12+\qquad 16\qquad-5 \\\\
=-17+16\\\\
=-1$$

.
 Jun 4, 2015
 #1
avatar+107456 
+10
Best Answer

$$\\\frac{(-6)^2}{(-3)}+\qquad\frac{-8}{(-1/2)}\qquad-5 \\\\
=\frac{36}{(-3)}+\qquad-8\div\frac{-1}{2}\qquad-5 \\\\
=\frac{36}{(-3)}+\qquad 8\div\frac{1}{2}\qquad-5 \qquad $A neg divided by a neg = a pos$\\\\
=-12+\qquad 8\times\frac{2}{1}\qquad-5 \\\\
=-12+\qquad 16\qquad-5 \\\\
=-17+16\\\\
=-1$$

Melody Jun 4, 2015
 #2
avatar+65 
+5

Thanks alot, Melody!

 Jun 5, 2015
 #3
avatar+107456 
+5

You are very welcome Lunar   

 Jun 6, 2015

7 Online Users